تعليم الخط العربي وتأثيره في ترقية مهارة الكتابة - Moh. Rozy Zamroni (Universitas Negeri Malang, 2023)
This study aims to explain about learning Arabic calligraphy and its influence in improving students' writing skills. The method used in this research is quantitative research with techniques for collecting data from existing sources both from books or journals and then reviewed to get a more actual understanding.: design, learning and evaluation. In the implementation of the calligraphy learning process, students are quite interested in the material presented, so that the learning process runs very interestingly and the students pay attention to the material presented by the teacher تهدف هذه الدراسة إلى شرح كيفية تعلم الخط العربي وأثره في تحسين مهارات الكتابة لدى الطلاب. الطريقة المستخدمة في هذا البحث هي البحث النوعي بتقنيات لجمع البيانات من المصادر الموجودة سواء من الكتب أو المجلات ثم مراجعتها للحصول على فهم أكثر واقعية: التصميم والتعلم والتقييم. في تنفيذ عملية تعلم الخط يهتم الطلاب باهتمام تام على المواد المقدمة، بحيث تتم عملية التعلم بشكل ممتع للغاية وينتبه الطلاب إلى المواد التي قدمها المعلم.